The Role of Provost in Enforcing Internal Police Discipline: A Juridical Study at Battalion C Pelopor, Mobile Brigade Corps (Brimob), South Sulawesi Regional Police - AM, A. Muallim; Razak, Askari; Badaru, Baharuddin (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study examines the juridical function of the Provost in enforcing disciplinary law within the Indonesian National Police at Battalion C Pelopor of the Mobile Brigade Corps, South Sulawesi Regional Police. The research applies a sociological or empirical legal approach that analyzes law not only as written norms but also as legal behavior in institutional practice. Data were obtained through literature review, interviews, and observation involving police personnel, academics, legal practitioners, and members of the public. The findings show that the Provost serves as a strategic internal supervisory body responsible for monitoring, investigating, and enforcing disciplinary rules among police officers. The juridical basis of this function derives from Law Number 2 of 2002 on the Indonesian National Police and Government Regulation Number 2 of 2003 on Police Disciplinary Regulations. The study also reveals that disciplinary enforcement operates through systematic procedures such as reporting, investigation, and leadership decision-making. Its effectiveness, however, is influenced by legal substance, professionalism of officers, availability of facilities, community expectations, and organizational culture. Strengthening the capacity and independence of Provost personnel, improving legal awareness and professional ethics, and enhancing transparency in disciplinary processes are necessary to support institutional accountability and public trust in the police